Enterprise Architecture Implementation Scholastic Learning Zone Literacy Improvement St. Kristoforus 2 High-School - Yudianto, Tri; Indrajit, Eko; Makmur, Amelia; Dazki, Erick (Sinkron : jurnal dan penelitian teknik informatika, 2024)
This research aims to explore the transformation of Enterprise Architecture in the implementation of a Scholastic Learning Zone for the improvement of learners' literacy at Santo Kristoforus 2 High School. The background of this research is based on the importance of literacy as the primary foundation in learning, as well as the need to integrate innovative educational technology. The main objective of the research is to understand how the implementation of Enterprise Architecture can support the implementation of the Scholastic Learning Zone effectively and efficiently. The research method used is a qualitative approach with a case study at Santo Kristoforus 2 High School, involving in-depth interviews with educators, direct observation, and analysis of related documents. The results showed that the implementation of Enterprise Architecture significantly contributed to improving the structure and process of education, thus supporting the improvement of learners' literacy. Key findings include improved accessibility of learning resources, school administration efficiency, and increased learner engagement in the learning process. Additionally, the implementation facilitated the creation of eBooks for learning materials, further enhancing literacy by providing students with readily accessible and interactive content. The conclusion of this study shows that the transformation of Enterprise Architecture in the implementation of the Scholastic Learning Zone not only improves literacy but also strengthens the education system. Further research is recommended to test this model in different educational contexts to extend the validity of the findings.